The relationship between self-esteem and the employees’ s motivation in work of state organizations - Rus, Mihaela; Sandu, Mihaela Luminița; Cheval, Claudia Gabriela; Ene, Bianca Elena (Technium Social Sciences Journal, 2022)
Work feeds many different aspects of people’s lives. It influences self-identity, self-esteem and opportunities for personal development. Over time, researchers have paid considerable attention to the concept of self-esteem, trying to understand its influence on other psychological constructs such as motivation and performance at work, anxiety and risk-taking. In most companies today, motivating employees to perform to their full potential in the workplace is one of the key elements in modern human resource management. It is believed that when an employee is motivated, he will generally be satisfied with the job, which will have an impact on self-esteem.Abraham Maslow was the first modern psychologist to move away from the idea that people are passive and driven only by physiological impulses and external stimuli. His theory of human motivation suggested that people are motivated by both psychological and physiological needs. Motivation is the basic force that explains why people engage in certain behaviors. Some people seem to be driven by an increased interest in their work, a deep level of pleasure in what they do, and others seem to be more motivated by external incentives in their work, such as promotion, salary, recognition, and so on.An individual’s self-esteem, formed around work and organizational experiences, plays a significant role in determining employees’ motivation, attitudes and work-related behaviors. Self-esteem refers to an individual’s overall self-assessment of his or her skills. In this sense, self-esteem is a personal assessment that reflects what people think about themselves as individuals. At the same time, self-acceptance is essential for mental health and performance at work. Lack of the ability to accept oneself unconditionally can lead to a variety of difficulties in the workplace.As a general objective, the paper aims to measure the relationship, the connection between self-esteem and motivation at work, with an emphasis on the branches of motivation.The relatively low number of participants and the fact that all individuals belong to the urban environment can be mentioned as limitations of the study.